2013
DOI: 10.1002/jmv.23786
|View full text |Cite
|
Sign up to set email alerts
|

Viruses associated with influenza‐like‐illnesses in Papua New Guinea, 2010

Abstract: Influenza-like-illness can be caused by a wide range of respiratory viruses. The etiology of influenza-like-illness in developing countries such as Papua New Guinea is poorly understood. The etiological agents associated with influenza-like-illness were investigated retrospectively for 300 nasopharyngeal swabs received by the Papua New Guinea National Influenza Centre in 2010. Real-time PCR/RT-PCR methods were used for the detection of 13 respiratory viruses. Patients with influenza-like-illness were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…This result suggests that the case definitions of ILI detect not only influenza but also other virus infections, particularly RSV and HRV infections. Influenza viruses were one of the most common viral agents in the tested samples, similar to the results reported previously [ 8 , 27 29 ]. RSV was another commonly occurring virus in this study.…”
Section: Discussionsupporting
confidence: 90%
“…This result suggests that the case definitions of ILI detect not only influenza but also other virus infections, particularly RSV and HRV infections. Influenza viruses were one of the most common viral agents in the tested samples, similar to the results reported previously [ 8 , 27 29 ]. RSV was another commonly occurring virus in this study.…”
Section: Discussionsupporting
confidence: 90%
“…In the one study identified as providing information on influenza in Papua New Guinea, 29.3% of samples from patients with ILI received by the Papua New Guinea National Influenza Centre in 2010 had laboratory‐confirmed influenza, of which 43.2% were influenza type B …”
Section: Resultsmentioning
confidence: 99%
“…In studies reporting age‐stratified data, the proportions of influenza caused by influenza type B were higher among children aged between 1 and 10 years than in older age groups . In 17 studies using comparable age strata, between 10.9% and 90% of all influenza B cases were detected in children aged <10 years (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Regarding the age-related distribution of multiple pathogens, our observation that patients under 5 years of age were more likely to have multiple detections, is almost in accordance with the eliminated previously published data. [33,3537] Nevertheless, Tramuto et al have also noticed that most of their patients with multiple etiology were adults and elderly. [24]…”
Section: Discussionmentioning
confidence: 99%